The effect of Sustainable Frugal Innovations on agriculture productivity - Simbarashe Nhokovedzo (THOT Publishing House, 2021)
The dynamism of the agricultural sector environment requires continuous innovation to cope with emerging challenges. Sustainable frugal innovations (SFIs) are an attempt to scale above sustainability challenges in agriculture. Zimbabwe, like many emerging economies has embraced the application of sustainable frugal innovations in farming. The study sought to assess the impact of sustainable frugal innovations on the growth of the agriculture sector. In this study, Agriculture growth is defined asincrease in productivity hence the terms growth and productivity are used interchangeably. A quantitative research was adopted to gather data from agriculture experts. Preliminary correlation tests were run on economic, environmental and social sustainability against productivity. The relationship between sustainable frugal innovations and agriculture productivity was tested through regression analysis. The findings revealed positive relationship between sustainable frugal innovation and agriculture growth. These findings provide vital insights to motivate creation and adoption of sustainable frugal innovations. Application of sustainable frugal innovations is expected to increase efficiency in production and processing of agriculture produce hence grow the agriculture sector